Penerapan Sistem Manajemen Pengadaan Barang di PT.Unefeco Kuala Tanjung - Afdolli Ilman Ritonga; Nuri Aslami (Jurnal Publikasi Ilmu Manajemen, 2024)
PT.UNEFECO is a company operating in the service sector which acts as a contractor, where this role is entrusted by PT.INALUM to PT.UNEFECO to carry it out. Therefore, PT.UNEFECO to carry out this work requires the procurement of goods or materials. The aim of the application research The goods procurement management system at PT UNEFECO is to evaluate the effectiveness and efficiency of the goods procurement management system used and obtain information about the advantages and disadvantages of the system. The data collection techniques used in this research are observation, interviews and literature study. The results of this research are that during the month the author was at PT Unefeco, the author encountered a problem, namely that there was often a lack of communication between suppliers and the company in procuring goods. such as inappropriate delivery times and often the number of goods ordered is not appropriate, resulting in sub-optimal activities of workers/employees. So it can be concluded that the company is still not optimal or efficient in carrying out its goods procurement management system.